Stochastic Electrical Detection of Single Ion-Gated Semiconducting Polymers - Nieuwenhuis, Ab F (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 The Authors. Advanced Materials published by Wiley-VCH GmbH.